A Study on Biocompatible Polymer-Based Packaging of Neural Interface for Chronic Implantation - Park, HyungDal; Choi, Won suk; Oh, Seonghwan; Kim, Yong-Jun; Seok, Seonho; KIM, JIN SEOK (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This paper proposed and verified the use of polymer-based packaging to implement the chronic implantation of neural interfaces using a combination of a commercial thermal epoxy and a thin parylene film. The packaging's characteristics and the performance of the vulnerable interface between the thermal epoxy layer and polyimide layer, which is mainly used for neural electrodes and an FPCB, were evaluated through in vitro, in vivo, and acceleration experiments. The performance of neural interfaces-composed of the combination of the thermal epoxy and thin parylene film deposition as encapsulation packaging-was evaluated by using signal acquisition experiments based on artificial stimulation signal transmissions through in vitro and in vivo experiments. It has been found that, when commercial thermal epoxy normally cured at room temperature was cured at higher temperatures of 45 degrees C and 65 degrees C, not only is its lifetime increased with about twice the room-temperature-based curing conditions but also an interfacial adhesion is higher with more than twice the room-temperature-based curing conditions. In addition, through in vivo experiments using rats, it was confirmed that bodily fluids did not flow into the interface between the thermal epoxy and FPCB for up to 18 months, and it was verified that the rats maintained healthy conditions without occurring an immune response in the body to the thin parylene film deposition on the packaging's surface.